Baptism and Cognition in Romans 6-8: Paul's Ethics beyond 'Indicative' and 'Imperative' - Siikavirta, Samuli (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2015)
Paul's 'indicative' and 'imperative': a review of scholarship -- Paul's ethics in context -- Baptismal status and identity -- Cognition of the baptismal state -- The baptismal foundation of Paul's ethics